Load Capacity and Bending Strength of Double-Acting Friction Stir Welded AA6061 Hollow Panels - Nurul Muhayat; Muhammad Budi Utama; Ericha Dwi Wahyu Syah Putri; Eko Prasetya Budiana; Aditya Rio Prabowo; Yohanes P. D. S. Depari; . Triyono (Salehan Institute of Higher Education, 2024)
Aluminum alloy hollow panels are essential components in both civil and mechanical structures, such as building floors or large vehicle platforms. They enhance rigidity while staying lightweight and conserving material volume. In its application, this panel must be joined using welding methods. One common issue encountered in aluminum welding is the formation of porosity defects. Solid-state welding methods like Friction Stir Welding (FSW) can be a solution to address this problem. The FSW joining process on hollow panels cannot be completed in one welding operation due to their thickness. The FSW process must be performed on both surfaces, which requires a relatively long time. Therefore, FSW needs to be developed into a Double-acting FSW that utilizes two tools simultaneously. These two tools introduce two sources of heat input, pressing force, and friction-stirring, resulting in a novel response that needs further research. This study delves into the impact of welding speed variations in Double-Acting FSW on the load capacity and bending strength of AA 6061 hollow panel joints. Welding speeds of 20, 30, and 40 mm/min were tested alongside rotational speed (1500 rpm), tilt angle (2°), and shoulder diameter (24 mm). It was discovered that reducing welding speed enhances both load capacity and bending strength. Notably, specimens welded at 20 mm/min exhibited a load capacity of 15.61 kN and bending strength of 52 MPa, highlighting the potential of slower speeds for superior weld performance. Doi: 10.28991/CEJ-2024-010-08-018 Full Text: PDF